(untitled) (Third Sector Social Economic Review, 2023)
Customer incivility has a vital importance in organizational life. Although it is an old issue for the service sector, it has not been fully covered in the local literature. There are studies on rude behavior from one employee to another, from manager to staff, in the context of workplace incivility. However, it can be observed that there is a lack of studies on customer incivility in the local literature. The study aims to theoretically evaluate the impact of customer incivility on the service sector employee and determine the possible consequences on employees, customers, and organizations in light of relevant research in the literature. Moreover, the sectoral factors that make customer incivility possible are mentioned in the study. Lastly, the importance of dealing with customer incivility is emphasized. In this context, the study aims to fill a gap in the local literature, and for service organizations, it reveals the harmful effects of customer incivility and its possible organizational consequences.